PENENTUAN JUMLAH ALAT PEMADAM API RINGAN (APAR) OPTIMAL (STUDI KASUS: GEDUNG FAKULTAS TEKNIK UNIVERSITAS MULAWARMAN) - Febriana, Ria; Dianati Fathimahhayati, Lina; Amelia Pawitra, Theresia (Jurnal Rekavasi, 2022)
The Faculty of Engineering, one of the faculties at Mulawarman University, has the potential for fire to occur. The application of fire extinguishers in the engineering campus environment is still deficient, therefore this research’s purpose are to find out how the application of fire extinguishers that have been applied at the Faculty of Engineering and how to give improvements to the implementation that is not appropriate. This research refers to the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia No. Per04/Men/1980 and Regulation of the Minister of Public Works No.26 of 2008 to determine the suitability of the application of fire extinguisher. Meanwhile, a reference based on NFPA 10 is used to determine the number of appropriate fire extinguisher needs in the Faculty of Engineering. The results obtained from the 20 elements of the assessment carried out on 69 fire extinguishers at the Faculty of Engineering obtained an average of 59.47% according to the standard. From the calculation, it was found that the need for all fire extinguishers in the Faculty of Engineering building is 41 fire extinguishers which previously had 69 fire extinguishers. This amount also reduces maintenance costs from Rp8.775,000, - to Rp5.625.00, -. Suggestions for improvement are given to the extinguishers that aren’t accordance with ther application refers to the standards used, reducing the number of extingushers, allocationg 3 fire extinguishers to other building and storing 28 unused fire extinguishers in the warehouse.